Augustine and his critics : essays in honour of Gerald Bonner - Bonner, Gerald; Dodaro, Robert, 1955-; Lawless, George (Routledge, 2000)
Augustine of Hippo (AD 354-430) is arguably the most controversial Christian thinker in history. His positions on philosophical and theological concerns have been the subjects of intense scrutiny and criticism from his lifetime to the present. Augustine and his Critics gathers twelve specialists' responses to modern criticisms of his thought, covering: personal and religious freedom; the self and God; sexuality, gender and the body; spirituality; asceticism; cultural studies; and politics. Stimulating and insightful, the collection offers forceful arguments for neglected histori.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustin, -- saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430; RELIGION -- Christianity -- General.; RELIGION -- Christian Theology -- Systematic.; Electronic books.; Festschriften; Festschriften.